THE EFFECT OF EDUCATION LEVEL AND WORK EXPERIENCE ON EMPLOYEE PERFORMANCE AT TIRTA INDRA RENGAT REGIONAL DRINKING WATER COMPANY - Fitria Ningsih; Said Afriaris (JURNAL MANAJEMEN DAN BISNIS, 2021)
This research was conducted at the Regional Drinking Water Company (PDAM) Tirta Indra Rengat, Indragiri Hulu Regency. The address is Jl. R.A. Hakim of the village of Kampung Besar, the city of Rengat District.The purpose of this study is to determine the effect of the variable level of education and Work Experience on Employee Performance at the Regional Drinking Water Company (PDAM) Tirta Indra Rengat, Indragiri Hulu Regency. Sampling used the Surakhmad formula (Winarno Surakhmad) with 44 samples as respondents. The analytical method used is quantitative descriptive method, data analysis is carried out by path analysis (with the help of the IBM SPSS Statistics Program Version 21.00). The results of the study indicate that the level of education and work experience has an effect on employee performance at the Regional Water Company (PDAM) Tirta Indra Rengat, Indragiri Hulu Regency. Education level affects employee performance at Tirta Indra Rengat Regional Drinking Water Company (PDAM) Indragiri Hulu Regency and Work Experience has no effect on Employee Performance at the Regional Water Company (PDAM) Tirta Indra Rengat, Indragiri Hulu Regency.